2010
DOI: 10.1007/s11627-009-9263-1
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of soybean (Glycine max L. Merrill) through direct somatic embryogenesis from the immature embryonic shoot tip

Abstract: We describe here a simple and efficient system of soybean (Glycine max L. Merrill) regeneration through direct somatic embryogenesis by using immature embryonic shoot tips (IEST) as explants. The cultivar Kaohsiung 10 (cv. K10) used in this study did not show embryogenic response either from mature seed-derived explants (cotyledon, embryonic tip, leaf, shoot and root) or immature cotyledons. However, it showed a high percentage (55.8%) of somatic embryo (SEm) formation from the IEST excised 2-3 wk after flower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 48 publications
1
12
0
1
Order By: Relevance
“…Thereafter, in vitro regenerated shoot tip explants were taken for genetic transformation studies. Shoot tip explants are potent explants used for genetic transformation studies in other economically important plants like corn (Cao et al, 2014;Zhong and Sticklen, 2000), cotton (Gould et al, 1998;Lei et al, 2012), soybean (Loganathan et al, 2010), jute (Saha et al, 2014), eucalyptus (Silva et al, 2011) etc. showing their suitability for genotype independent genetic transformation.…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, in vitro regenerated shoot tip explants were taken for genetic transformation studies. Shoot tip explants are potent explants used for genetic transformation studies in other economically important plants like corn (Cao et al, 2014;Zhong and Sticklen, 2000), cotton (Gould et al, 1998;Lei et al, 2012), soybean (Loganathan et al, 2010), jute (Saha et al, 2014), eucalyptus (Silva et al, 2011) etc. showing their suitability for genotype independent genetic transformation.…”
Section: Resultsmentioning
confidence: 99%
“…Loganathan et al (2010) menunjukkan bahwa genotipe sangat berpengaruh dalam keberhasilan embriogenesis somatik. Beberapa genotipe lebih responsif terhadap media kultur dibandingkan genotipe lainnya (Thiruvengadam et al, 2006;Hiraga et al, 2007;Yang et al, 2009).…”
Section: Cunclassified
“…Such variability's can partially be overcome by some modifications in embryogenesis and regeneration protocols (Bailey et al, 1993). Recently Loganathan et al (2010) reported the somatic embryogenesis from immature embryonic shoot tips on MS medium containing 6% sucrose, 2,4-D and amino acids. The embryos efficiently regenerated into shoots on hormone free MS medium containing charcoal.…”
Section: Soybean Tissue Culture Strategiesmentioning
confidence: 99%